Determinants of the Portuguese External Imbalances: The Lens of Post-Keynesian Economics - Barradas, R.; Alcobia, J. (REM Working Paper Nº 2024/334, 2024)
Portugal has historically displayed strong external imbalances, which have already resulted in three requests for international financial assistance from the International Monetary Fund, the European Commission and the European Central Bank. Stemming from the framework of mainstream economics literature, these institutions imposed demanding austerity measures based on internal devaluation, huge wage restraint policies and strict control on government balance in order to contain the Portuguese domestic demand and to promote Portuguese external competitiveness. Accordingly, Portuguese labour costs have registered a general decreasing trend, and government balance has substantially improved in the last four decades, but the Portuguese external imbalances remain unsolved, which suggests that we need to go beyond the conventional economic literature in order to better ascertain the right determinants of external imbalances. This paper aims to contribute to the current theoretical debate about the determinants of the external imbalances by relying on the post-Keynesian economics literature and performing a time series econometric analysis for Portugal from 1988 to 2023. Results evidence that the fall of labour costs and the surge of both stock and housing prices are the main drivers behind the Portuguese external imbalances over the last four decades.